Protein restriction during lactation causes transgenerational metabolic dysfunction in adult rat offspring - Vargas, Rodrigo; Martins, Isabela Peixoto; Matiusso, Camila Cristina Ianoni; Casagrande, Raiana Aparecida; Zara, Camila Benan; Huppes de Souza, Anna Carolina; Horst, William Pereira; Sieklicki, Taina Cristine; Becker, Tania Cristina Alexandrino; Lucredi, Naiara Cristina; Comar, Jurandir Fernando; Malta, Ananda; et al. (Frontiers in Nutrition, 2023)
Protein restriction during lactation can induce metabolic dysfunctions and have a huge impact on the phenotype induced in the offspring later in life. Objective: We tested whether the effects of maternal low-protein diet (LP) can be transmitted to F2 generation and increase their vulnerability to dietary insult at adulthood. Methods: Female Wistar rats (F0) were fed either a low-protein diet (LP; 4% protein) during the first two weeks of lactation or a normal-protein diet (NP; 23% protein). Their female offspring (F1 generation) were maintained on a standard diet throughout the experiment. At adulthood, female F1 offspring from both groups (i.e NP-F1 and LP-F1 group) were bred to proven males, outside the experiment, to produce F2 offspring. Male F2 offspring from both groups (i.e NP-F2 and LP-F2 group) received standard diet until 60 days old, when then they received either a normal fat (NF; 4,5% fat) or high fat diet (HF; 35% fat) by 30 days. Results: At 90 days old, LPNF-F2 offspring had increased in lipogenesis and fasting insulinemia compared to NPNF-F2, without alteration in insulin sensitivity. HF caused increased gluconeogenesis and displayed glucose intolerance in LPHF-F2 compared to LPNF-F2, besides damage in lipid metabolism as steatosis grade 3, higher body weight, fat pad stores and hepatic lipid content. Conclusion: We concluded that the F0 maternal protein-restriction diet during lactation could induce a transgenerational effect on glucose and liver metabolism in F2 generation, making liver’ offspring more vulnerable to nutritional injury later in life.